Basic Training of Student’s Outdoor Club Increases Muscle Mass after Five Weeks of Exercise in Males - Novie Salsabila; M. Rizal Chaidir; Setiawan Setiawan (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Aerobic and anaerobic exercises, may lead to increase muscle mass. The aim of this study was to determine the change in muscle mass during basic training of students’ outdoor club.Methods: This was an observational analytic study to college students who joined basic training of students’ outdoor club for 19 weeks. Subjects consisted of 17 male and 15 female students, measured five times consecutively by using Body Fat/Hydration monitor scale, with Bioelectrical Impedance Analysis principle. Data collection was performed five times, from February to July 2012 in Bandung. Statistical analysis was processed using Analysis of Variance (ANOVA).Results: The result in males showed the mean 43.35±3.15 on the initial measurement. The muscle mass further increased significantly after five, ten, fifteen, and nineteen weeks of exercise (43.73±3.18 (p<0.05); 44.07±2.97 (p<0.05); 44.08±2.84 (p<0.05); 44.72±2.78 (p<0.05); all data vs 43.35±3.15) respectively. In females, there was increased of muscle mass although not all were statistically significant. The baseline was 37.77±2.00 with increased muscle mass after five, ten, fifteen, and nineteen weeks of exercise (37.78±2.06 (p>0.05); 38.08±1.67 (p>0.05) ; 38.23±1.52 (p>0.05) ; 38.61±1.52 (p<0.05) vs 37.77±2.00) respectively.Conclusion: Basic training of student’s outdoor club increases muscle mass significantly after five weeks of exercise in males, but not in femalesKeywords: Basic training, Bioelectrical Impedance Analysis, hypertrophy, muscle mass, students outdoor clubDOI: 10.15850/amj.v2n1.445